Konsep Sabar dalam Perspektif Pendidikan Tasawuf dan Relevansinya terhadap Resiliensi Psikologis - Shabrina; Umi Nur Kholifah (Al-Kindi, 2025)
This study aims to examine the concept of patience from the perspective of Sufism education and its relevance to developing psychological resilience in individuals in the modern era. Using a qualitative approach based on literature, this study examines the thoughts of classical and contemporary Sufis regarding patience as a process of purifying the soul, self-control, and fortitude in facing the dynamics of life. Sufism education views patience not merely as the ability to restrain oneself, but rather as a spiritual practice that fosters deep awareness, inner calm, and active submission to the will of God. These values ​​align with elements of psychological resilience, such as emotional regulation, cognitive flexibility, and the ability to recover from adversity. The results of this study indicate that internalizing patience through Sufism practices such as self-reflection, self-control, and self-control can strengthen individual resilience by building mutually reinforcing spiritual and psychological resilience. Thus, the concept of patience in Sufism education has a significant contribution as an alternative approach to developing psychological resilience in various educational contexts and everyday life.